Comparative analysis of the taxonomies in use for didactic planning of Language and Literature in Secondary Education (Revista INTEREDU11, 2021)
This work is the result of a comparative study and analysis between the taxonomies of Benjamin Bloom, SOLO de Biggs, Lorin Anderson, L. Dee Fink and Robert J. Marzano. This analysis shows common elements and differentiators, associated and related to teaching-learning processes. The incorporation of both, content and learning activities, from the subject “Lenguaje y Comunicación” were considered for the extrapolation of taxonomies. At the end of the text is presented a proposal that allows to show the adaptation and use of different systems in a single process or unity, thus managing to strengthen both, the quality of students’ learning processes and the teaching practice.